A handbook of natural beauty - Bakhru, H.K. (DR)
Summary: "Beauty and health go hand in hand. The finest cosmetics in the world cannot disguise the effects of poor nutrition, lack of sleep and exercise or too much stress. Beauty comes from within and it is reflected in clear skin, sparkling eyes, glossy hair and a fit, trim body.